2011
DOI: 10.1590/s0104-11692011000500020
|View full text |Cite
|
Sign up to set email alerts
|

Noise at the Neonatal Intensive Care Unit and inside the incubator

Abstract: The goal was to identify sound pressure level (SPL) at the neonatal intensive care unit (NICU) and inside the incubator of a teaching hospital of a public university from São Paulo -SP, Brazil. SPL inside the NICU and the incubator were measured using four dosimeters in January/2010. SPL at the NICU varied from 52.6 dBA to 80.4 dBA and inside the incubator, from 45.4 dBA to 79.1 dBA. SPL both at the NICU and inside the incubator are above the recommended values, but levels were higher at the NICU than inside t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 16 publications
2
21
0
2
Order By: Relevance
“…Studies have found evidence for high levels of sound pressure in NICU and inside the incubators (6,8,13) and have indicated the deleterious eff ects on the health of neonates, health care professional and family, although there is s ll a scarcity of studies in the Brazilian and interna onal Nursing literature on the subject here researched.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have found evidence for high levels of sound pressure in NICU and inside the incubators (6,8,13) and have indicated the deleterious eff ects on the health of neonates, health care professional and family, although there is s ll a scarcity of studies in the Brazilian and interna onal Nursing literature on the subject here researched.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term eff ects of noise may be shown in the form of diffi cul es in hearing, thinking, conversing, reading, wri ng, spelling or calcula ng, aff ec ng the child´s social, emo onal, intellectual and linguis c development (8) .…”
Section: Introductionmentioning
confidence: 99%
“…This also results in staff having to talk louder. [2] Research on nurses' understanding of and approaches towards the sound sources are, however, limited. Children admitted to a PICU is a small and vulnerable group that need sleep and rest to grow and develop.…”
Section: Introductionmentioning
confidence: 99%
“…[3] This needs to be considered, as caring means meeting children's needs, relieving their pain, avoiding suffering and promoting growth and health. [11] High noise levels have been shown to increase stress in neonates [2] that lead to frustration or anxiety. [7] In fact, high sound levels can be the difference between life and death for a critically ill child due to the risk of high blood pressure, stimulated by stress deriving from high sound levels or other negative stimulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation